Multicultural Identity Crisis in Bharati Mukherjee’s Novel Jasmine - Seema Parveen ,; Prof. Tanveer Khadija, (The Creative Launcher, 2021)
This paper intends to explore the transformations with disintegration literary pieces of Bharati Mukherjee has gained a milestone as she brings out the segregation experienced by the immigrants of South Asian Countries. Through her novels, she voices her personal life experiences to show the reconstructing shape of American Society. She centrally locates her emphasis on the women characters their struggle for identity, their harsh experiences and their final emergence as the self- assertive, self opinioned individuals free from fear imposed on them. The list of Diasporic writer is too long and the root of Diaspora is so deep. Through the novel Jasmine, Bharati Mukherjee focuses the multicultural identity of a woman. This paper is an effort to portray the bitter experiences of homelessness, displacement, oppression and exploitation of protagonist Jasmine.